(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The oil and gas industry is characterized by many complexities and specificities of business operations. The above is also reflected in the identification of value components, and the understanding of their interrelationships. In order to have an effective value management, it is especially important to follow up on the movements in key financial indicators and qualitative factors which impact the creation of financial results. This paper presents the theoretical basis in order to identify the most important qualitative value components in oil and gas companies. Therefore, the specificities of all sectors within this industry are highlighted in order for them to be related to the key financial factors influencing the creation of stable cash flows. For this purpose, a cluster analysis of selected key financial factors has been performed using self-organizing neural networks. Connecting identified qualitative value components affecting cash flows with the financial parameters through which they are reflected, creates a framework for developing an effective value management model. Keywords: Oil and gas industry, business value components, free cash flow, self-organizing neural networks